Combined Pharmacological Modulation of Translational and Transcriptional Activity Signaling Pathways as a Promising Therapeutic Approach in Children with Myocardial Changes - Kamenshchyk, A. V.; Belenichev, I.; Oksenych, V.; Kamyshnyi, O.; Каменщик, Андрій Володимирович; Бєленічев, Ігор Федорович (My University, 2024)
Myocardial hypertrophy is the most common condition that accompanies heart development in children. Transcriptional gene expression regulating pathways play a critical role both in cardiac embryogenesis and in the pathogenesis of congenital hypertrophic cardiomyopathy, neonatal posthypoxic myocardial hypertrophy, and congenital heart diseases. This paper describes the state of cardiac gene expression and potential pharmacological modulators at different transcriptional levels. An experimental model of perinatal cardiac hypoxia showed the downregulated expression of genes responsible for cardiac muscle integrity and overexpressed genes associated with energy metabolism and apoptosis, which may provide a basis for a therapeutic approach. Current evidence suggests that RNA drugs, theaflavin, neuraminidase, proton pumps, and histone deacetylase inhibitors are promising pharmacological agents in progressive cardiac hypertrophy. The different points of application of the above drugs make combined use possible, potentiating the effects of inhibition in specific signaling pathways. The special role of N-acetyl cysteine in both the inhibition of several signaling pathways and the reduction of oxidative stress was emphasized.
Keywords: myocardial hypertrophy; children; gene expression signaling pathways; pharmacological modulation; heart